The construction of policy in the context of divorce and relationship breakdown - Hasson, Ezra (2002)
In January of 2001 the Government announced its intention to repeal Part 11 of the Family Law Act 1996. Originally scheduled for implementation in 2000, the Act had provided for fundamental changes to English divorce law, including removing matrimonial 'fault' from the divorce process, and encouraging mediation as the preferred method of dispute resolution.